Bank risk during the financial crisis: do business models matter? - Yener Altunbas; David Marqués-Ibá\~nez; Simone Manganelli (European Central Bank (ECB), 2011)
We exploit the 2007-2009 financial crisis to analyze how risk relates to bank business models. Institutions with higher risk exposure had less capital, larger size, greater reliance on short-term market funding, and aggressive credit growth. Business models related to significantly reduced bank risk were characterized by a strong deposit base and greater income diversification. The effect of business models is non-linear: it has a different impact on riskier banks. Finally, it is difficult to establish in real time whether greater stock market capitalization involves real value creation or the accumulation of latent risk.
Keywords: G21; G15; E58; G32; 330; Bank Regulation; bank risk; Basle III; business models; financial crisis